Long stay effects in the Antarctic on ultrastructure and platelet function in people with load hypoxic - E. V. Rozova; Y. V. Moiseyenko (Ukrainian Antarctic Journal, 2013)
The work is devoted to the study of changes in the platelets ultrastructure (in winterers) in hypoxic stimulation before and after a long stay in Antarctica. It is shown that the ultrastructural parameters of platelets in Antarctic winterers significantly modified. Changes in tension indicates a platelet function and probably progenitor cells. Reaction of winterer’ platelets to hypoxic stimulation have the characteristic features. They can be considered as a compensatory-adaptive. The mechanisms of such transformations are characterized by the increase of the functional activity of organelles due to a moderate degree of edema, which may indicate an increase in energy production and activation of glycolysis.